An Analysis Of Good Governance Implementation In The Sipraja Application To Improve The Public Service Bureaucratic System In Sidoarjo - Olifia, Ike Rizky; Febrianti, Sofi Putri (Institut Riset dan Pengembangan Indonesia, 2025)
This study aims to assess the extent to which the principles of good governance are applied in using the SIPRAJA (Sidoarjo Public Service Information System) application, especially in the context of digitizing public services in the field of personnel in Sidoarjo Regency. The approach used is qualitative, with data collection methods through interviews, direct observation, and document analysis. This study uses secondary data as a source of information. The results of the study indicate that SIPRAJA has adopted several principles of good governance, such as openness of information (transparency), performance responsibility (accountability), and community involvement in the service process (participation). Even so, there are still obstacles such as low public understanding of digital technology and limited supporting facilities available. The use of SIPRAJA has been proven to be able to accelerate services and increase accuracy in managing personnel data. Overall, this application has been running in line with the principles of good governance, but there needs to be an improvement in terms of technological infrastructure and education for the community so that the digitalization of services can run more optimally in the future